2017
DOI: 10.1007/s00253-017-8225-5
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the bioprospecting and biotechnological potential of white-rot and anaerobic Neocallimastigomycota fungi: peptidases, esterases, and lignocellulolytic enzymes

Abstract: Fungi constitute an invaluable natural resource for scientific research, owing to their diversity; they offer a promising alternative for bioprospecting, thus contributing to biotechnological advances. For a long time, extensive information has been exploited and fungal products have been tested as a source of natural compounds. In this context, enzyme production remains a field of interest, since it offers an efficient alternative to the hazardous processes of chemical transformations. Owing to their vast bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(11 citation statements)
references
References 81 publications
0
11
0
Order By: Relevance
“…No fungal growth was noticed on wood disks in the strictly anaerobic digester. It has been reported that biogas production can be improved in the presence of white rot fungi and anaerobic fungi such as Neocallimastigomycota [23] due to their ability to degrade complex polymers, and that the cellulose degradation activity of anaerobic fungi is Although significant weight loss occurred in the experiment for all treatments (p < 0.0001, t-test of log 10 transformed data), there were no significant differences seen in weight loss among treatments. Nevertheless, wood disks placed in the strictly anaerobic tanks lost the least amount, averaging 6.3 g on a dry weight basis whereas all other treatments lost over 7 g dry weight.…”
Section: Waste Degradationmentioning
confidence: 90%
See 1 more Smart Citation
“…No fungal growth was noticed on wood disks in the strictly anaerobic digester. It has been reported that biogas production can be improved in the presence of white rot fungi and anaerobic fungi such as Neocallimastigomycota [23] due to their ability to degrade complex polymers, and that the cellulose degradation activity of anaerobic fungi is Although significant weight loss occurred in the experiment for all treatments (p < 0.0001, t-test of log 10 transformed data), there were no significant differences seen in weight loss among treatments. Nevertheless, wood disks placed in the strictly anaerobic tanks lost the least amount, averaging 6.3 g on a dry weight basis whereas all other treatments lost over 7 g dry weight.…”
Section: Waste Degradationmentioning
confidence: 90%
“…No fungal growth was noticed on wood disks in the strictly anaerobic digester. It has been reported that biogas production can be improved in the presence of white rot fungi and anaerobic fungi such as Neocallimastigomycota [23] due to their ability to degrade complex polymers, and that the cellulose degradation activity of anaerobic fungi is increased in the presence of methanogens [24]. Analyses are planned to identify this fungus as well as determine how bacterial and other microbial populations may have been affected by micro-aeration.…”
Section: Waste Degradationmentioning
confidence: 99%
“…This finding suggests this termite possesses a functional mycobiota in its gut that contributes to the lignocellulose digestion. Neocallimastigales comprises anaerobic highly active lignocellulolytic fungi of the gastrointestinal tract of herbivores, which has also been reported in termites (Lee et al, 2015;da Silva et al, 2017).…”
Section: Discussionmentioning
confidence: 88%
“…This finding may be related to the herbivorous characteristics of these piglets. Fungi are known for their ability to depolymerize complex molecular structures and are used in the degradation of lignocellulosic biomass, improvement of animal feed digestibility, biogas and bioethanol production, and various other applications [ 26 ]. Previous sequencing results have shown that Basidiomycota and Ascomycota were dominant phyla in the gastrointestinal tract of humans and animals [ 27 ].…”
Section: Discussionmentioning
confidence: 99%